2021
DOI: 10.1039/d1nj01678d
|View full text |Cite
|
Sign up to set email alerts
|

Recent quinone diazide based transformations via metal–carbene formation

Abstract: Diazo quinone or quinone diazide, a class of compound has been recently extensively utilised to introduce naphthol moities into the hydrocarbons or nitrogen-containing heterocycles under transition metal catalysis. The reactions...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 86 publications
0
14
0
Order By: Relevance
“…Carbene insertion to C-H bonds, as one of the hot topics in C-H functionalization area, has aroused rapidly increasing interests. Due to the leading contributions by Davies, [24][25][26] Doyle, 4,6 Wang, 7,27 Fox, 28 and others, important advances have recently been achieved, some of which were highlighted, 11,[29][30][31] and commented in prospects, [32][33][34][35] book chapters, 36,37 books, 38,39 and personal accounts. [24][25][26][27][28][40][41][42][43] In the recent reviews regarding C-H functionalization and diazo compounds, carbene insertion to C-H bonds is usually composed as an important section.…”
Section: Yong-gui Zhoumentioning
confidence: 99%
“…Carbene insertion to C-H bonds, as one of the hot topics in C-H functionalization area, has aroused rapidly increasing interests. Due to the leading contributions by Davies, [24][25][26] Doyle, 4,6 Wang, 7,27 Fox, 28 and others, important advances have recently been achieved, some of which were highlighted, 11,[29][30][31] and commented in prospects, [32][33][34][35] book chapters, 36,37 books, 38,39 and personal accounts. [24][25][26][27][28][40][41][42][43] In the recent reviews regarding C-H functionalization and diazo compounds, carbene insertion to C-H bonds is usually composed as an important section.…”
Section: Yong-gui Zhoumentioning
confidence: 99%
“…2 Strategically, the use of metal− carbene complexes generated from quinonediazides/diazonaphthalen-2(1H)-ones as aryl synthons is beneficial due to their unique reactivity and minimum waste production. 3 Often, these carbenes offer phenol/naphthol moieties that are electrophilic at their generally nucleophilic ortho and para positions. Since Baran and Dao's pioneering work on olefin functionalization with these highly electrophilic carbenes, 4 significant progress has been noticed in this area.…”
Section: ■ Introductionmentioning
confidence: 99%
“…There are various reports on directed and nondirected insertion of the metal complexes of the corresponding carbene (quinoid-carbene) into the C(sp 2 )-H bonds. 5−8 Recently, few studies were reported where predictable intramolecular C(sp 3 )-H insertion were carried out under transition metal catalysis using quinoid-carbene species. 9 Subsequently, our group developed a Rh(III)-catalyzed intermolecular C(sp 3 )-H arylation of model substrates such as 8-methyl quinoline scaffolds via a migratory insertion-based approach.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations